1997
DOI: 10.1097/00007632-199701010-00018
|View full text |Cite
|
Sign up to set email alerts
|

Potential Large Vessel Injury During Thoracolumbar Pedicle Screw Removal

Abstract: Great care must be taken during the removal of broken pedicle screws to prevent injury to surrounding structures. Additionally, indications for the removal of distal screw fragments must be carefully established. Instruments designed to capture the end of the distal screw fragment through an interference fit may allow anterior screw migration to occur, particularly in osteoporotic bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 9 publications
0
42
0
2
Order By: Relevance
“…Although the rate of neurovascular complications associated with screw misplacement in scoliosis surgery usually reported to be almost 0% [3,[5][6][7], reports on serious complications associated with screw misplacement have been published since the introduction of this procedure [8][9][10][11]. As segmental pedicle screw fixation has become a widely used method in scoliosis corrective surgery, the knowledge about the pedicle morphometry has become increasingly essential.…”
Section: Introductionmentioning
confidence: 99%
“…Although the rate of neurovascular complications associated with screw misplacement in scoliosis surgery usually reported to be almost 0% [3,[5][6][7], reports on serious complications associated with screw misplacement have been published since the introduction of this procedure [8][9][10][11]. As segmental pedicle screw fixation has become a widely used method in scoliosis corrective surgery, the knowledge about the pedicle morphometry has become increasingly essential.…”
Section: Introductionmentioning
confidence: 99%
“…The L4 roots are in the lateral part of the vertebral body and a screw which is at least 45 mm long and it is not introduced with an angle in the inferior part of the pedicle could break the lateral cortical and come into contact with the L4 root and damage it. Jendrisak 15 reported a case of spontaneous rupture of the aorta because of an anterior implant and Vanichkachorn et al 16 reported a case of an implant removal because of the implant protrusion which affected the aorta. Lim et al 17 reported a case of pseudoanaeurism of the aorta after an instrumentation with pedicular screws in T12 and L3.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous papers have reported on the hazards and potential complications associated with pedicle screw insertions, but complications in conjunction with implant removal are rarely reported [13]. Vanichkachorn et al [13] report one case of potential large vessel injury during the removal of a broken pedicle screw. They conclude that routine removal of pedicle screws, especially screw fragments is not indicated and may result in rare but significant complications.…”
Section: Discussionmentioning
confidence: 99%
“…The risks associated with the use of pedicle screws, such as neurological problems, dural laceration, screw and rod breakage, screw loosening, and loss of correction due to implant failure, are well established and have been extensively reviewed [1,7,14]. However, there is a paucity of reports on the complication potential of implant removal of pedicle screw systems [13].…”
Section: Introductionmentioning
confidence: 99%